A new energetically optimized power supply system for a mobile robot platform, using ultracapacitors and batteries to ensure both ultra-fast charging and autonomy - Arantes, Carlos (2015)
The smallest charging times required by fully discharged conventional batteries are some tens of minutes. This is an important limitation for mobile robot platforms. A previous paper already validated the possibility of integrating ultracapacitors and batteries in the same system. However, it has some significant limitations: 1) It works with an ultracapacitors module or a battery, but it does not work with both devices at the same time; 2) It requires an external dedicated charging station; 3) It is not possible to take profit from a part which is non-negligible - of the energy previously stored in the ultracapacitors. This paper presents a new power supply system for mobile robot platforms that has been developed in order to overcome these limitations. Its main goals are evaluating the feasibility of: 1) Fully integrating batteries and ultracapacitors, working simultaneously as energy-storing devices, with the aim of enabling a mobile robot platform to achieve a reasonable autonomy after a very reduced charging time and considerable autonomy when there are no charging time constraints; 2) Installing all the system in the mobile robot platform, avoiding the use of an external dedicated charging station; 3) Extracting almost all the energy previously stored in the ultracapacitors. Both simulation results and experimental results are presented.